From horticulture to agriculture: New data on farming practices in Late Chalcolithic western Anatolia - Maltas, Tom; Sahoglu, Vasif; Erkanal, Hayat; Tuncel, Riza (Elsevier, 2022)
We combine stable isotope analysis of crop remains with functional ecological analysis of their associated weeds to investigate arable farming strategies at Late Chalcolithic Bakla Tepe and Liman Tepe, western Anatolia. Our results reveal 'low-input' cultivation practices at both sites, with cereals grown on plots with low soil fertility that received low to moderate levels of manuring. In contrast, water supply was unlikely to have been a limiting factor to crop cultivation. Land management strategies were adapted to the tolerances of different crops, with pulses more intensively manured than cereals at Liman Tepe and barley cultivated on drier soils than glume wheats at both sites. This attests to a spatial differentiation in crop cultivation that resembles the practices of recent farmers in the Aegean engaged in extensive systems of land use. Expanded forms of these agricultural systems were used to amass agrarian wealth by elites occupying the citadels of later Early Bronze Age (EB/EBA) western Anatolia, suggesting that the agroecological foundations of this phenomenon were already in place by the late fourth millennium BC. In contrast to the pronounced wealth inequality visible in EBA citadels, however, we suggest that extensive land use fostered productive equality through cooperation between small-scale households in the Late Chalcolithic. It was only with the emergence of more extended domestic units in the EBA, capable of greater autonomy in arable farming, that disparities in production could be maintained over the long-term. This shift may have contributed to the emergence of social structures designed to dampen arable wealth inequality in the EBA.
Keywords: Turkey; Archaeobotany; Stable isotope analysis; Functional weed ecology; Agriculture; Crop husbandry